The influence of social media on behavior and characteristics of teenagers - Setyaningsih, Margaretha Ratih; Wijayanti, Lucia Wiwid (Proceedings of International Conference on Research in Education, 2025)
Social media use in the current digital era is widespread among all groups, especially teenagers. Social media certainly influences the behavior and characteristics of its users, both positively and negatively. This paper aims to examine the effects of social media use on the behavior and characteristics experienced or acquired by adolescent users. This paper was conducted using a literature review method sourced from several journals and articles circulating online. The results of several journals and articles regarding the influence of social media on the behavior and characteristics of adolescents indicate that social media has both positive and negative effects. Some positive effects include expanding friendship networks, improving communication skills, and serving as a forum for interpersonal discussion. Some negative effects include making adolescents addicted to social media, leading to cyberbullying, and triggering deviant behavior. Based on the literature review, it can be concluded that social media does indeed have both positive and negative effects on the behavior and characteristics of adolescent users. Positive effects include improving communication skills and expanding relationships, while negative effects include addiction and triggering deviant behavior.